Investigação do mecanismo de ação do ácido α-lipóico (ALA) em via dopaminérgica no modelo de mania induzido por D-anfetamina - Cavalcante, Letícia Régia Lima (2020)
α-lipoic acid (ALA) is a naturally occurring antioxidant and anti-inflammatory compound that has been widely studied as an adjuvant in the treatment of various neuropsychiatric diseases. Despite the growing list of clinical applications, ALA's mechanisms of action remain elusive. In this context, the pharmacological treatment of bipolar affective disorder (BD) has several limitations, mainly related to its adverse effects, highlighting the need to search for new therapies. Based on this, the present study was proposed to investigate the action of ALA in the dopaminergic pathway using the mania model induced by D-amphetamine (ANF). Swiss SPF (specific pathogen free) female mice (20-25g), from the vivarium of the Nucleus for Research and Development of Medicines (NPDM) of the Federal University of Ceará (UFC), were used. The animals were treated with ANF (2 mg / kg, ip) or saline (ip) for 14 days and olanzapine (OLA, 2 mg / kg, ip), ALA (100 mg / kg, vo) or both from the 8th to the 14th day of the experimental protocol. The animals' weight was recorded on the 1st and 14th days of treatment, immediately before the administrations. Two hours after the last amphetamine administration, the animals were submitted to open field, elevated plus maze, social interaction and Y-maze behavioral tests. Subsequently, the animals were euthanized by decapitation and the hippocampus (HC) and striatum (ST) were dissected to investigate the levels of dopamine (DA) and 3,4-dihydroxyphenylacetic acid (DOPAC) in HC and to measure the gene expression of dopamine D2 and D3 receptors in ST. It was observed that the administration of ALA in association with OLA in female mice submitted to the ANF-induced mania model was effective in preventing the weight gain caused by OLA in these mice. In addition, this study demonstrated the reversal of hyperlocomotion and exploratory behavior in the open field induced by chronic administration of ANF through treatments with OLA, ALA or the two drugs combined, and reversal of risk behavior induced by ANF in the elevated plus-maze through the administration of ALA alone (in the length of stay in the open arms or number of head dips) or combined with OLA (only in the number of head dips). The chronic administration of ANF did not change the sociability and working memory of these animals. The neurochemical analysis revealed an increase in the DOPAC/DA ratio in HC in the ANF group compared to the control. In the ST, we observed an increase in the expression of the D2 receptor induced by OLA, which was reversed in the treatment with OLA and ALA in combination, and an increase in the expression of the D3 receptor induced by OLA or ALA, also reversed in the treatment with the two drugs in combination. Finally, the computational study revealed a possible interaction of ALA at the orthosteric site of dopamine D2 and D3 receptors, through a different pattern than that observed for DA or OLA. Together, these results demonstrate the reversal of behavioral changes induced by ANF through the use of ALA, alone or combined with OLA, and support the evidence about the direct action of ALA on dopaminergic neurotransmission, in addition to indicating a preferential action of this molecule on the orthosteric site of D3 receptors. Since ALA already has proven efficacy in the clinic in reversing several neuropsychiatric symptoms, this study sought to deepen the knowledge about its different sites and mechanisms of action, and may be useful in expanding its clinical use.